2010
DOI: 10.1186/1749-8090-5-99
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two protective lung ventilatory regimes on oxygenation during one-lung ventilation: a randomized controlled trial

Abstract: BackgroundThe efficacy of protective ventilation in acute lung injury has validated its use in the operating room for patients undergoing thoracic surgery with one-lung ventilation (OLV). The purpose of this study was to investigate the effects of two different modes of ventilation using low tidal volumes: pressure controlled ventilation (PCV) vs. volume controlled ventilation (VCV) on oxygenation and airway pressures during OLV.MethodsWe studied 41 patients scheduled for thoracoscopy surgery. After initial tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
0
25
1
Order By: Relevance
“…However, others have reported that PCV results in poorer oxygenation [20, 21] and the effect of PCV on oxygenation is one of the areasof greatest controversy. We hypothesized that PCV is associated with improved oxygenation and lower inspiratory pressure in comparison with VCV.…”
Section: Introductionmentioning
confidence: 99%
“…However, others have reported that PCV results in poorer oxygenation [20, 21] and the effect of PCV on oxygenation is one of the areasof greatest controversy. We hypothesized that PCV is associated with improved oxygenation and lower inspiratory pressure in comparison with VCV.…”
Section: Introductionmentioning
confidence: 99%
“…During PCV the clinician should titrate the inspiratory pressure to the measured tidal volume, but the inspiratory flow and flow waveform are determined by the ventilator as it attempts to maintain a square inspiratory pressure profile (18). Thus, advantage of PCV is a lower peak airway pressure, but disadvantage is that tidal volume delivery increases and decreases with changes of patient's compliance (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Methodologically, as primary graft dysfunction grades 3 and 4 are synonymous with ALI and acute respiratory distress syndrome (ARDS), our study was based on the protective ventilation concept adapted from the literature . A comparison between volume and pressure‐controlled ventilation was included due to previous studies demonstrating that lower peak pressures may minimise acute lung injury . Similar to Montes et al ,.…”
Section: Discussionmentioning
confidence: 99%